Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Air Minum dalam Kemasan Merek AQUA melalui Minat Beli sebagai Variabel Intervening : (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang) - Jesika Erliana; Rauly Sijabat; Ika Indriasari (Yayasan Literasi Sains Indonesia, 2025)
The purpose of this study was to examine the influence of brand image, product quality, and purchase intention on purchasing decisions for AQUA brand bottled drinking water. This study adopts a causal approach to explanatory research, namely research that aims to provide an explanation in the form of a causal relationship between several concepts or several variables or management strategies that are developed. The data collection method in this study used a questionnaire. The sampling technique was carried out using non-probability random with a purposive sampling approach. The sample used in this study was 100 respondents. The data analysis technique in this study used SmartPLS3. The results of this study indicate that brand image does not have a significant effect on purchasing decisions, product quality does not have a significant effect on purchasing decisions, brand image does not have a significant effect on purchasing interest, product quality has a significant effect on purchasing interest, purchasing interest has a significant effect on purchasing decisions, brand image does not have a significant effect on purchasing decisions through purchasing interest, product quality has a significant effect on purchasing decisions through purchasing interest.